1964
DOI: 10.1002/app.1964.070080306
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of polyurethane to thermal degradation

Abstract: SynopsisThe labile hydrogen of the carbamate group is primarily responsible for color develop ment in the thermal degradation of polyurethane. Replacement of this hydrogen by an alkyl group prevents back-dissociation. Accordingly, a number of N-substituted polyurethanes were prepared, including the methyl, benzyl, bensoyl, acetyl, and the (N'-phenylamido) derivatives. Comparative studies at 150-155OC. showed that the N-methyl and N-bemyl polymers possess outstanding stability under the condition of our testing. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previous studies for the N‐substitution of PEOPU using the catalyst/solvent condition of NaH/DMF reported that the backbone could be degraded resulting in the poor properties of the final polymer, and the extent of N‐substitution could be limited to a maximum of approximately 50% for the N‐methylation reaction and a maximum of approximately 15% for the N‐substitution reaction longer than methyl 10. Spectroscopic results indicated that not only the N‐methyl PEOPU but also the butyl PEOPU and N‐MOEO PEOPU were successfully prepared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies for the N‐substitution of PEOPU using the catalyst/solvent condition of NaH/DMF reported that the backbone could be degraded resulting in the poor properties of the final polymer, and the extent of N‐substitution could be limited to a maximum of approximately 50% for the N‐methylation reaction and a maximum of approximately 15% for the N‐substitution reaction longer than methyl 10. Spectroscopic results indicated that not only the N‐methyl PEOPU but also the butyl PEOPU and N‐MOEO PEOPU were successfully prepared.…”
Section: Resultsmentioning
confidence: 99%
“…During thermoplastic processing at temperatures above 200 °C, they are split back into starting polyols and isocyanates; they also show inadequate hydrolytic stability and electrochemical stability 3–6. N‐Substitution of PU was used to overcome the preceding disadvantages and improve various typically desired properties of the materials, such as enhanced fire retardancy, flexibility, solubility, and so forth 7–12. N‐Modification of PUs is generally carried out in two steps, that is, preliminary metalation of the starting PU with catalyst and subsequent treatment of the obtained urethane polyanion with alkyl halogenides.…”
Section: Introductionmentioning
confidence: 99%
“…A methylene group in MDI is also susceptible to oxidation via a proton abstraction mechanism, involving auto-oxidation of the aromatic urethane groups to a form of quinoneimide [17]. Resistivity of the urethane group against thermal, oxidative and UV degradation can be improved by substitution of the liable hydrogen atom by groups such as the methyl and benzyl groups [18].…”
Section: Monomers Used For Synthesis Of Urethane Copolymers Aromatic mentioning
confidence: 99%
“…The development of WB resin materials from vegetable oils is a challenging task due to their hydrophobic nature. The most common way to solubilize a vegetable oil in water is to introduce highly hydrophilic ionic groups such as carboxyl, amine, anhydride or amide and subsequent neutralization with acid or base [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%